Agile Performance Management in Romanian NGOs: Catalyst for a transformative shift towards a more vibrant third sector or a forced adaptation of a for-profit construct? - MIERTOIU, Alina-Denisa (2025)
This book, while not claiming to be able to put to rest the battle described above once and for all, it aims at understanding the actual state of organizational performance management practices and goal-setting practices deployed by Romanian non-profits, as well as understand the main challenges NGOs face when measuring and improving performance, in order to design and pilot a performance management framework that fits in the given context and addresses the main limitations, therefore aiming to provide that happy medium mentioned above. This tool, although still containing the measurement component, should be able to provide more flexibility to NGO managers, including having them and other NGO members deciding on the measurements that are important for them and would have the team define success for their specific context without following a set of pre-defined measures.